Assessment of Coumarin Levels in Ground Cinnamon Available in the Czech Retail Market - Jana Blahová; Zdeňka Svobodová (The Scientific World Journal)
The objective of this study was to determine the coumarin content of ground cinnamon purchased from retail markets in the Czech Republic. No sample was labelled with information on the botanical source, but, in some cases, the countries of origin were specified. For comparison, a single cinnamon sample imported directly from a plantation in Sri Lanka that came from Cinnamomum verum was analyzed. Results from 60 ground cinnamon samples comprising twelve brands confirmed a high content of coumarin, with mean levels ranging from 2 650 to 7 017 mg · kg−1. The high coumarin content confirmed that these cinnamon samples obtained from cassia cinnamon were in contrast to the sample from Sri Lanka, which was coumarin-free.